Recognizing sufism : contemplation in the Islamic tradition - Buehler, Arthur F.
Shows that the vast majority of Sufi practice, both historically and in the contemporary world, has little or nothing to do with a esoteric transcendence but is rather focused on contemplative activity. Such practice might involve art, music, devotional shrine visitation--even politics and psychology. Discussing the origins of Sufism; the development of Sufi lineages (via three founder figures); Sufi lodges and the role of Sufism in colonial resistance; Sufi poetry; Sufi shrines, and Sufism in the West, Buehler rescues his topic from the idea that it means only union with the divine. --From publisher description